Типовість розв'язності деяких задач оптимального керування - Семенов, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Let E be a real Banach space, X a nonempty weak compact subset of E, B a closed convex subset of E such that 0 belongs int B, and f : X → R be a bounded from above weak upper semicontinuous functional. It is proved that the set of all y belongs E, for which the problem f(x)+μβ(x − y) → sup x belongs X, where μβ is the Minkowski functional of B, has a solution, contains an Gδ-set dense in E. This result is used for proving the generic solvability optimal control problems for linear systems.